Intra-individual Comparison of High-Relaxivity versus Standard Macrocyclic Gadolinium Agents for Detecting Hepatic Micrometastases at 3.0 T - Linda Purnama; Adolfo Rawlings; Abdullah Assagaf (Phlox Institute: Indonesian Medical Research Organization, 2026)
Introduction. Hepatic micrometastases smaller than 10 mm critically influence oncologic staging and eligibility for curative metastasectomy, yet the sub-centimetre sensitivity of standard gadolinium-enhanced MRI is limited. High-relaxivity macrocyclic gadolinium-based contrast agents (GBCAs) generate higher lesion-to-liver contrast-to-noise ratio (CNR) and may improve detection. We compared a high-relaxivity versus a standard macrocyclic GBCA at equimolar dose within the same patients. Methods. In this prospective intra-individual diagnostic-accuracy study reported per STARD 2015 at a tertiary hospital in Palembang, Indonesia, 48 adult oncology patients underwent two 3.0-T liver MRI examinations 2 to 7 days apart in randomised contrast order (standard gadoterate meglumine versus a high-relaxivity macrocyclic agent, 0.1 mmol/kg). Two gastrointestinal radiologists blinded to agent and clinical and reference data read images independently. A composite reference standard (histopathology and ≥6-month multiphasic imaging follow-up) defined 134 metastatic lesions. Sensitivity, specificity, AUC (DeLong), likelihood ratios, Cohen kappa and McNemar tests were computed. Results. The high-relaxivity agent increased CNR by 12.2 units (48.5 versus 36.2; p<0.001). Per-lesion sensitivity rose to 94.8% (95% CI 89.6–97.4) from 82.8% (75.6–88.3), and micrometastasis sensitivity to 88.7% from 66.1% (McNemar p<0.001). The area under the ROC curve was 0.929 (0.893–0.966) versus 0.821 (0.757–0.886; DeLong p=0.003), and the negative likelihood ratio improved to 0.06. Inter-reader kappa was 0.89 versus 0.83. Specificity was comparable (84.5% versus 89.7%; p=0.41). Conclusion. At equimolar dose, the high-relaxivity macrocyclic GBCA significantly improved CNR and sub-centimetre hepatic metastasis detection without meaningful loss of specificity, a gain that may alter oncologic management. High-relaxivity agents are recommended for high-risk hepatic staging.